Clinicopathologic characteristics of patients with vulvar cancer treated between 1994 and 2017 at the University Medical Centre Maribor: Klinično-patološke značilnosti pacientk z rakom zunanjega spolovila, zdravljenih v obdobju od 1994 do 2017 v Univerzitetnem kliničnem centru Maribor - Gavrič Lovrec, Vida; Kozar, Nejc; Takač, Iztok; Stangler Herodež, Špela (Acta Medico-Biotechnica, 2021)
Purpose: Vulvar cancer is one of the rarest forms of cancer. Vulvar cancer represents 3%–7% of all gynecologic cancers. Eighty percent of patients with vulvar cancer are > 60 years of age. The vulvar cancer, analyze the epidemiology, and describe the clinical characteristics, treatment modalities, and factors that influence the development of vulvar cancer. Methods: This retrospective study included patients treated at the University Medical Centre Maribor for vulvar cancer between 1994 and 2017. Patient demographics, disease characteristics, clinical features, histologic findings, and type of therapy were recorded. Associations among various demographic factors, tumor characteristics, treatments, and risk factors of vulvar cancer were evaluated. Results: We collected data from 124 patients between 22 and 92 years of age. The average age of the patients was 71 years. Six different tumor types were identified, of which the most common histologic type of vulvar cancer was squamous cell carcinoma. Forty-five patients were tested for the presence of HPV types, which was confirmed in 71% (32/45) of the tested patients.Conclusion: Squamous cell carcinoma was the most common form of vulvar cancer in patients treated at the University Medical Centre Maribor. Undoubtedly, one of the risk factors for vulvar cancer is HPV infection. HPV 16 was the most frequently diagnosed HPV type in our patients. For more comprehensive and more representative conclusions, data from other medical centers in Slovenia should be included.
Keywords: vulvar cancer; epidemiology; histology; HPV